Political Consumerism and Cultural Identity : A Study of SMEs in Taiwan's Bubble Tea Industry - Chang, Ching-Ling; Martínez Pantoja, Yadira Ixchel; San José Iglesias, Rafael; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This study investigates the phenomenon of political consumerism in Taiwan’s bubble tea industry by conducting both quantitative and qualitative researches. Quantitative data were collected through consumer surveys, revealing moderate correlations between consumers’ political attitudes and their consumption decisions. It indicated the dual role of political consumerism not only a reward but a punishment mechanism for the brands. Qualitative insights were gathered through semi-structured interviews with SMEs, addressing how they perceive and strategically respond to political consumerism. The interviews pointed out the importance of authenticity, trust, and local identity in shaping brand loyalty and business performance, while as well revealing SMEs’ cautious approach to express political stances due to their limited risk tolerance.
Vedoucí práce: Yadira Ixchel Martínez Pantoja
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses